Factors Influencing Behaviors for Delaying Progression of Kidney Impairment Among Patients with Uncontrolled Type 2 Diabetes Mellitus - Poowilai, Suchada; Supruang, Jariya; Kasipul, Taweesuk (Journal of health and health management, 2025)
This study investigated the behaviors and factors of preservation of kidney function among patients with uncontrolled type 2 diabetes mellitus. The sample consisted of 124 patients with uncontrolled type 2 diabetes mellitus who were visiting a non-communicable chronic disease clinic (NCD) and were chosen through simple random sampling. The research instruments utilized in the study were general information questionnaires, perceived susceptibility, perceived benefits, perceived barriers, perceived self-efficacy, cues to action, and kidney function preservation behaviors. The instruments were reliable with Cronbach’s alpha coefficients of .83, .94, .89, .88, .85, and .73, respectively. Data was analyzed using descriptive statistics and multiple regression analysis. The results indicated that the overall score of kidney function preservation behaviors was moderate (M = 3.23, SD = 0.61). Cues to action, especially support from health personnel, and perceived self-efficacy in performing kidney function preservation behaviors significantly predicted 32.6% of the variance in kidney function preservation behaviors (R2 = 0.326, p < .001). Based on these findings, nurses should develop programs to promote kidney function preservation behaviors, emphasizing cues to action, particularly healthcare personnel support, and enhancing perceived self-efficacy.